The Innovative Guidance and Spiritual Religious Counseling Materials Based on The Values of The Teachings of Sheikh Mutamakkin at The Ornaments of The Kajen Mosque - Yuliyatun Yuliyatun; Sugiyo Sugiyo; Sunawan Sunawan; Anwar Sutoyo (International Conference on Science, Education, and Technology, 2022)
It is important for a counselor to have a comperehensive understanding of the concept of human and everything that surrounds human’s life in order to become a mentally, psychologically and spiritually healthy person. The development of guidance and counseling materials needs to be expanded continuously because of human complexity with its multidimensionality. The purpose of this study is to obtain guidance and counseling materials contained in the principles of the teachings of Sheikh Ahmad Mutamakkin through the ornaments of the Kajen Mosque which contains teaching messages regarding the human process of achieving mental health. This study was conducted using a qualitative approach, an ethnographic model with an exploratory content analysis procedure. The data sourced from the ornaments and the previous study related to the study of Kajen mosque ornaments from previous researchers. The result of the study shows that the teachings contained in the ornaments of the Kajen mosque by Sheikh Ahmad Mutamakkin can be used as a source of knowledge and value in developing guidance and counseling service materials, especially those based on religious spirituality. The results of this study can be used as a framework for counselors' thinking in providing guidance and counseling services, especially those based on Islamic religion.